Liver Failure in a Chinese Cystic Fibrosis Child With Homozygous R553X Mutation - Li, Haiyan; Lin, Li; Hu, Xiaoguang; Li, Changchong; Zhang, Hailin (Frontiers in Pediatrics, 2019)
Cystic fibrosis (CF) is a relatively rare disease in Asians with various clinical characteristics, including CF-associated liver disease (CFLD), which is a common early non-pulmonary complication. This case report describes a Chinese CF patient harboring a homozygous nonsense mutation (c.1657C>T, p.R553X) who was failure to thrive and had intermittently diarrhea during the first year after birth. Liver function test of the patient showed the mildly and intermittently elevated alanine aminotransferase (ALT) levels ranging from 70 U/L to 92 U/L and aspartate aminotransferase (AST) levels ranging from 80 U/L to 90 U/L, which began at 8 months of age and lasted for 4 years without CF diagnosis. In addition, abdominal computed tomography (CT) revealed diffuse fatty inﬁltration of the liver at 4 years old and gradually developed hepatic cirrhosis. Subsequently, cirrhosis rapidly progressed with obvious splenomegaly and pancreatic insufficiency and the patient died of liver failure with coagulopathy by the age of 6 years old. Pediatricians should remain vigilant to avoid failure to diagnose CF, the occurrence of which may be underestimated, and pay greater attention to the patients with atypical clinical manifestations in Asian countries.